The Role of Electronic Word of Mouth (E-WOM) in Formation Consumer Attitudes towards Health Service Providers (A Survey Study in Lattakia City) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Social networking sites are among the platforms that have great popularity among consumers, especially as they constitute a vital source of information for them, which contributes to forming and changing their Attitudes, through its most important tools represented by the Electronic Word of Mouth E-WOM, which is the most influential communication tool among consumers during all stages of purchase. Hence, the research came to study the role of the Electronic Word of Mouth E-WOM in formation consumer Attitudes in Lattakia cityWhere the researcher designed an electronic questionnaire,  And publishing it on social media, targeting the residents of the city of Lattakia only, and the necessary analyzes and descriptions were performed using the SPSS 23 program. The most important results of the research were the existence of a fundamental role for the reliability of the Electronic Word of Mouth E-WOM on social media sites, in formation  consumer attitudes towards health service providers. As for the quality, and  density of the Electronic Word of Mouth on social media, it did not play a fundamental role in formation consumer attitudes. And based on the results of the research, a number of recommendations were proposed that, if applied, could contribute to improving consumer attitudes in the city of Lattakia towards health service providers.